1967
DOI: 10.2466/pms.1967.24.2.495
|View full text |Cite
|
Sign up to set email alerts
|

Field Dependence in a Geriatric Population

Abstract: Cross-sectional and longitudinal studies of field dependence by Witkin and his associates suggest a course of decreasing field dependency between childhood and adolescence or early adulthood. The present study is an initial attempt to explore changes in field dependency through adulthood and old age. Three groups of Ss, 17-, 30- to 39-, and 58- to 80-yr.-olds, were given three tests of field dependency, the body-adjustment, rod-and-frame, and embedded-figures tests. On each test field dependency increased sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1

Year Published

1969
1969
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 4 publications
3
33
1
Order By: Relevance
“…Men between 60 and 75 years of age, who were still working, have been reported to be significantly more field independent than their retired cohorts (Karp, 1967). Yet, other studies have found no significant differences in field dependence between younger and older adults (Panek, 1985;Schwartz & Karp, 1967).…”
Section: Field Independencementioning
confidence: 74%
See 1 more Smart Citation
“…Men between 60 and 75 years of age, who were still working, have been reported to be significantly more field independent than their retired cohorts (Karp, 1967). Yet, other studies have found no significant differences in field dependence between younger and older adults (Panek, 1985;Schwartz & Karp, 1967).…”
Section: Field Independencementioning
confidence: 74%
“…Field dependence appears to decline from 8 to 15 years of age, stabilizes, then in later life appears to increase (Panek, 1985;Schwartz & Karp, 1967;Witkin, Oltman, Raskin, & Karp, 1971). Men between 60 and 75 years of age, who were still working, have been reported to be significantly more field independent than their retired cohorts (Karp, 1967).…”
Section: Field Independencementioning
confidence: 99%
“…Furthermore, visual field-dependent individuals are more sensitive to peripheral visual information, such as motion and orientation cues (Amblard et al 1985;Isableu et al 1998;Streepey et al 2007). A shift towards greater visual field dependence has been reported in old adults (Eikema et al 2012;Kobayashi et al 2002;Marendaz 1984;Markus 1971;Panek et al 1978;Poulain et al 2004;Schwatz and Karp 1967;Slaboda et al 2011). However, the determinants leading to this age-related shift in frame of reference selection have not been well defined.…”
Section: Introductionmentioning
confidence: 91%
“…It has been shown that internal models modulate the perception of the vertical (Barra et al 2010), taking into account one's perception of the body's longitudinal (Z) axis, or Bidiotropic vector^ (Mittelstaedt 1983). Body verticality perception has been investigated in young and old adults (Barbieri et al 2010;Schwatz and Karp 1967) to examine the evolution of egocentric spatial orientation with age. These studies demonstrated alterations of the body schema with age, possibly due to somatosensory deficits (Boisgontier and Nougier 2013;Deshpande and Patla 2005;Shaffer and Harrison 2007;Woollacott 1993).…”
Section: Introductionmentioning
confidence: 99%
“…An individual child high in field independence relative to his or her peers at one age is likely to remain high relative to those peers at a later age, but all children become increas ingly field independent as a group (Witkin, Goodenough, and 4 Karp, 1967). This movement toeard field independence appears to stop somewhere before middle age, after which people tend to become increasingly field dependent as they grow older (Schwartz and Karp, 1967). However, Goldstein and Blackman (1978) warn that most studies linking advanced age with increasing field dependence have confounded age with infirmity.…”
mentioning
confidence: 99%